Implementasi Akad Syariah Dalam Surat Perjanjian Pada Produk KPR Syariah IB Hebat Di BPRS Dana Amanah Surakarta - Amir , Devid Frastiawan; Firdaus, Muhammad Irkham; Bilhaq, Aqil Mu'tasim (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2024)
BPRS Dana Amanah Surakarta is the second BPRS in Surakarta. The need for housing is a primary need and until now houses are still a rarity for most Indonesian people. Not everyone can afford to buy a house in cash. In connection with the collaboration between BPRS Dana Amanah Surakarta and PT Sarana Multigriya Finansial (Persero) as a secondary housing finance company, and in order to realize the community's need for home ownership, BPRS Dana Amanah Surakarta issued KPR Syariah iB Hebat product. Sharia Mortgage (KPR) is a type of service provided by BPRS to customers to obtain housing loan financing based on a sharia contract. This research aims to describe the implementation of sharia contract in the letter of agreement on KPR Syariah iB Hebat products at BPRS Dana Amanah Surakarta. This research used a qualitative approach, descriptive, field research. The results obtained, the implementation of contract agreements in BPRS must pay attention to legal aspects and positive legal regulations which have a very important position so that they can provide legal basis and prevent risks that have an impact on BPRS, on the other side, sharia principles must also be considered in implementing these agreements. The contract used in the KPR Syariah iB Hebat product at BPRS Dana Amanah Surakarta is a murabahah contract (Fatwa DSN-MUI No: 04/DSN-MUI/IV/2000 concerning Murabahah), istishna’ parallel (Fatwa DSN-MUI No: 22/DSN-MUI/III/2002 concerning Sale and Purchase of Istishna’ Parallel), and musyarakah mutanaqishah (Fatwa DSN-MUI No: 73/DSN-MUI/XI/2008 concerning Musyarakah Mutanaqishah). The provisions listed in the Fatwa DSN-MUI are then compiled into a letter of agreement, namely the letter of agreement that used murabahah without wakalah contract, murabahah bil wakalah contract, istishna’ paralel contract, and musyarakah mutanaqishah contract.